The Distribution of Junior High School Students’ Language Awareness Across English Oral Proficiency and Oral Corrective Feedback Preference - Prakoso, Ananda Rival; Munir, Ahmad; Mustofa, Ali (IJLECR (International Journal of Language Education and Cultural Review), 2024)
Language awareness is crucial in langage learning. It entails how language is perceived and used by the students. Language awareness cannot be separated from teaching learning process since there are many interactions between teacher and students in the class including performing oral competency, learning from mistake, giving and taking oral corrective feedback. Thus, it stil uncovered yet that language awareness is really matter in junior high school. This research tried to investigate the level of language awareness of junior high school students across their oral proficiency level. The study also aims to find out whether students’ level of language awareness is significantly different or not in their English oral language proficiency. In addition, the study also arried out to find out students type preference in receiving oral corrective feedback based on their language awareness level. This research is quantitative in nature. The data was collected from teacher archive in the form of students score and questionnaire. Then, the data was analyzed with the help of SPSS 20. The result showed that from 92 junior high school participant 35% of participants are in low level of language awareness; 32% in moderate level and 31% in high level. Based on the result, it can be concluded that majority of junior high school student are in low level of language awareness followed by moderate, and high. The analysis also showed that it retains the hypothesis of students’ language awareness level is similar across different English oral proficiency. Student with low, moderate, and high proficiency shows relatively similar level of language awareness level. Thus, the majority of students prefer explicit correction for oral corrective feedback type.